2018
DOI: 10.1002/hbm.24185
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of processing emotional prosody in unipolar depression

Abstract: Major depressive disorder (MDD) is characterized by a biased emotion perception. In the auditory domain, MDD patients have been shown to exhibit attenuated processing of positive emotions expressed by speech melody (prosody). So far, no neuroimaging studies examining the neural basis of altered processing of emotional prosody in MDD are available. In this study, we addressed this issue by examining the emotion bias in MDD during evaluation of happy, neutral, and angry prosodic stimuli on a five-point Likert sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 74 publications
0
10
0
Order By: Relevance
“…For alexithymia, a reduced neural response to emotional prosody within the right STG and the bilateral amygdala was shown ( Goerlich-Dobre et al, 2013 ). In a recent study, we demonstrated an increased neural activation of the amygdala during prosody processing in patients with MDD as compared to HC, while no differences between groups were found for the STG/MTG ( Koch et al, 2018 ). Although these studies suggest some variation regarding regional changes in activation, STG and amygdala emerge as most frequently involved brain areas across different psychiatric disorders.…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations
“…For alexithymia, a reduced neural response to emotional prosody within the right STG and the bilateral amygdala was shown ( Goerlich-Dobre et al, 2013 ). In a recent study, we demonstrated an increased neural activation of the amygdala during prosody processing in patients with MDD as compared to HC, while no differences between groups were found for the STG/MTG ( Koch et al, 2018 ). Although these studies suggest some variation regarding regional changes in activation, STG and amygdala emerge as most frequently involved brain areas across different psychiatric disorders.…”
Section: Introductionmentioning
confidence: 74%
“…Thus, the combined structural and functional results of our study indicate that the risk allele is associated with alterations of microstructure rather than functional activation of the amygdala as potential early neurobiological substrate for the development of affective disorders. Changes in functional activation and corresponding behavior as observed in depressed patients ( Koch et al, 2018 ) might occur only when the affective disorders already manifested itself as e.g. demonstrated for risk allele carriers with bipolar disorder ( Tesli et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Li et al ( 17 ) found that the abnormal activated brain regions including the dorsolateral prefrontal cortex and temporal gyrus were responsible for the altered performance during the explicit emotion task. In another study ( 18 ), the brain abnormalities primarily focused on the cerebellum, precentral gyrus, amygdala, insula, and others. Briceño et al ( 19 ) discovered a decreased activation on the precuneus in depressive patients during emotion-recognition tasks.…”
Section: Introductionmentioning
confidence: 99%